Normal Left Ventricular Size in Premature Newborns by the Echocardiographic Bullet Method - Bayle, Kenneth; Galotti, Geri; Nielsen-Farrell, Jill; Yang, Jie; Nielsen, James Cordry; Panesar, Laurie (American Journal of Perinatology, 2017)
Objective To define the normal range for a novel parameter of left ventricular (LV) size in premature neonates.Study Design We retrospectively analyzed echocardiographic imaging data to produce percentile nomograms and tabular data for Z-score calculation for LV end-diastolic volume (LVEDV) in premature neonates. The utility of LVEDV was compared with the current standard for LV size in patients who were treated for a patent ductus arteriosus (PDA).Results The mean gestational age and weight for the normal (n = 85) and PDA (n = 19) cohorts was 33 ± 5 weeks and 1.96 ± 1.0 kg and 25 ± 2 weeks and 0.87 ± 0.3 kg, respectively. The mean LVEDV of the PDA group (97.7 ± 22.2 mL/m^2.76) was significantly larger than that of reference group (63.0 ± 11.2 mL/m^2.76), p = 0.002. The sensitivity of LVEDV was better (68 vs. 11%) compared with LV dimension (the current standard) in detecting a large LV in the PDA patients. The LVEDV for our reference cohort (63.0 ± 11.2 mL/m^2.76) was smaller than the published normals (70.4 ± 9.1 mL/m^2.76, p < 0.001) for infants.Conclusion Echocardiographic LVEDV can now be utilized to determine the LV size in premature neonates. In patients with a PDA, an elevated LVEDV > +2 Z-scores can serve as objective data to aid in clinical trials and/or management decisions.
Keywords: left ventricular size; premature; patent ductus arteriosus; echocardiography